Regional Electricity Trade for Hydropower - Timilsina, Govinda R. (Taylor and Francis, 2021)
This study examines the importance of enhancing cross-border transmission interconnections and regional electricity trade to promote hydropower in the South Asia region and it quantifies the potential of hydropower development and trade under alternative scenarios. The paper shows that regional electricity trade is critical for the exploitation of the untapped hydropower resources in South Asia. It finds that hydropower capacity would increase by 2.7 times over the next two decades if a regional electricity market is developed. If a moderate carbon tax is added on top of it, hydropower capacity would be more than three times higher than the current level.